Syntactic Properties of Publicist Text Titles on the Internet - Mekhriniso Kadyrovna, Abuzalova; Dilnoza Rasulovna, Sobirova; Umidaxon Shavkatovna, Ahmadova (International Journal of Psychosocial Rehabilitation, 2020)
The titles of publicist texts published in Internet publications are linguistically analyzed in this article. The main focus here is on the syntactic features of the headings. During the years of independence, positive changes have occurred in the enrichment and renewal of the content of publicist texts, in enhancing information content and effectiveness. The focus of the media has been on language tools to maintain the originality of publicist text titles and enhance their advertising content. However, the linguistic features of headlines based on media, including internet publications, meet the requirements of methodological standards that haven't specifically been studied in Uzbek linguistics. The names of the publicist texts on the Internet are unique. In such texts, each selected header functions as nominative, informative, and promotional ones.